2020
DOI: 10.12681/jhvms.22234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indigenous Spore-Forming Probiotic as Feed Supplement on Performance and Safety in Broilers

Abstract: Probiotics colonize the intestine of animals and birds and provide useful effects on their performance and immune status. This study describes a high throughput screening and characterization of spore-forming bacteria from Iranian poultry farms with the aim to identify potential probiotic native Bacillus spp. and determine its effects on growth performance, hemato-biochemical parameters, immunity, intestinal microflora, morphology and MUC2 gene expression of broiler chickens. A total of 300 one-day-old female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…The observed actions could be attributed to the enhancing influence of B. subtilis probiotics on intestinal permeability and absorption functions. The results were consistent with those of He et al [50] and Hosseini et al [51], who reported that the inclusion of probiotics in broiler chicken rations could improve nutrient digestion, performance, antioxidant levels and activity, and intestinal morphology barriers against pathogenic microorganisms. Sobczak and Kozłowski [52] recorded synchronized results and found that B. subtilis (1×10 8 CFU/kg feed) improved performance, egg quality, and yolk cholesterol contents.…”
Section: Discussionsupporting
confidence: 92%
“…The observed actions could be attributed to the enhancing influence of B. subtilis probiotics on intestinal permeability and absorption functions. The results were consistent with those of He et al [50] and Hosseini et al [51], who reported that the inclusion of probiotics in broiler chicken rations could improve nutrient digestion, performance, antioxidant levels and activity, and intestinal morphology barriers against pathogenic microorganisms. Sobczak and Kozłowski [52] recorded synchronized results and found that B. subtilis (1×10 8 CFU/kg feed) improved performance, egg quality, and yolk cholesterol contents.…”
Section: Discussionsupporting
confidence: 92%
“…The following supporting information can be downloaded at: , Table S1: List of references and the respective experimental variables included in the meta-analysis [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]; Table S2: Descriptive statistics for predictive and response variables of jejunal and ileal gene expression (fold change) related to barrier function and immune response in broiler chickens at weeks 3 and 6 of life without pathogen challenge; Table S3: Descriptive statistics for predictive and response variables of jejunal and ileal histomorphology (fold change) in broiler chickens at weeks 3 and 6 of life without pathogen challenge; Table S4: Descriptive statistics for predictors and response variables of growth performance in broiler chickens at starter, finisher, and overall periods without pathogen challenge; Table S5: Descriptive statistics for predictive and response variables of jejunal, ileal, and cecal gene expression (fold change) related to barrier function in broiler chickens from weeks 2 to 5 with pathogen challenge; Table S6: Descriptive statistics for predictive and response variables of jejunal, ileal, and cecal gene expression (fold change) related to immune response in broiler chickens from weeks 2 to 4 of life with pathogen challenge; Table S7: Descriptive statistics for predictive and response variables of duodenal, jejunal and ileal histomorphology (fold change) in broiler chickens at weeks 2, 3, and 5 of life with pathogen challenge; Table S8: Descriptive statistics for predictors and response variables of growth performance in broiler chickens at starter, finisher, and overall periods with pathogen challenge.…”
mentioning
confidence: 99%